Skin Collagen and Thickness in Simple Obesity. Issue 5780 (16th October 1971) - Black, Martin M.; Bottoms, Eva; Shuster, Sam
Abstract : The effects of stretching of the skin on its collagen content and thickness have been studied in a group of subjects with chronic obesity. Despite the increase in skin surface a normal skin thickness, collagen content, and density were maintained. It is concluded that the skin stretching induced by prolonged obesity led to hypertrophy of collagen and that this had maintained both skin thickness and collagen content. It is not known whether this is due to enhanced synthesis or decreased degradation.